CNT@NiO/natural rubber with excellent impedance matching and low interfacial thermal resistance toward flexible and heat-conducting microwave absorption applications. Issue 3 (11th November 2020) - Zhou, Maofan; Wan, Gengping; Mou, Pengpeng; Teng, Shengjie; Lin, Shiwei; Wang, Guizhen
Abstract : Herein, CNT@NiO/natural rubber composites were fabricated to apply as flexible and heat-conducting microwave absorption materials. Abstract : The development of functional materials with both excellent electromagnetic wave absorption and high-efficiency thermal conductivity is becoming crucial and urgent due to the great progress in the miniaturization and integration of electronic components. Carbon nanotubes (CNTs) are very promising but still suffer from the disadvantages of poor microwave absorption and unsatisfactory heat conduction because of their impedance mismatching and interfacial thermal resistance. In this work, a modified atomic layer deposition (ALD) method is developed to fabricate CNT@NiO core shell structures in order to improve electromagnetic impedance matching and decrease interfacial thermal resistance. A uniform NiO coating can be grown with high efficiency onto the surface of CNTs by utilizing O3 and H2 O as oxygen source simultaneously. The CNT@NiO composites exhibit remarkably improved microwave absorption properties compared to the pristine CNTs. The optimal reflection loss reaches −43.6 dB at 17.5 GHz and have a thickness of only 1.3 mm. Moreover, the effective absorption frequency can be regulated by simply adjusting the cycle number of ALD NiO. The remarkable microwave absorption properties may be attributed to the multiple interfacial polarization, good impedance matching and multiple reflection and scattering owing to the synergistic effects from the well-balanced combination of CNT and NiO. In addition, the uniform NiO coating can serve as an intermediate layer between the matrix and CNTs to reduce the interface thermal resistance, resulting in the remarkable enhancement of thermal conductivity. With natural rubber (NR) as the matrix, the CNT@NiO/NR flexible composites can be potentially applied in the field of electronic packaging, microwave absorption and thermal management.